West Nile Virus Transmission in Resident Birds, Dominican Republic - Oliver Komar; Mark B. Robbins; Kaci Klenk; Bradley J. Blitvich; Nicole L. Marlenee; Kristen L. Burkhalter; Duane J. Gubler; Guillermo Gonzálvez; Carlos J. Peña; A. Townsend Peterson; Nicholas Komar (Emerging Infectious Diseases, 2003)
We report West Nile virus (WNV) activity in the Dominican Republic for the first time. Specific anti-WNV antibodies were detected in 5 (15%) of 33 resident birds sampled at one location in November 2002. One seropositive bird was <4 months old, indicating a recent infection.